Correlation between Clean Water Supply and Waste Management with Knowledge of Stunting - Anisa Indah Tetania; Witdiawati Witdiawati; Udin Rosidin (Journal of Nursing Care, 2023)
Stunting is an important global issue. One of the causes of stunting is the mother's inability to recognize it. Mother's knowledge will influence the way waste management and clean water supply. This study aimed to determine the relationship between knowledge about stunting and providing clean water and waste management in preventing stunting in Sukamulya Village. This research method is a quantitative correlation using secondary data. The population in this study were 55 mothers who had toddlers in Rancaekek District, Sumedang. The sampling technique used was total sampling. This study’s analysis used univariate and bivariate analysis with the Chi-Square test. The results of the study show that there is no relationship between the level of knowledge about stunting and the provision of clean water (p = 0.375), and there is no relationship between knowledge about stunting and waste management (p = 0.175). These results show that the level of knowledge is not a reference in the emergence of good behavior. Good knowledge influences behavior, but there are other aspects. Especially behavior towards the availability of clean water and waste management in preventing stunting. Further studies are needed by changing the variables used and the methods used.